Corrosion of Copper in Polluted Sea Water - K., Ravindran; A.G., Gopalakrisha pillai (Fishery Technology, 2025)
The corrosion potential and corrosion rate of electrolytic touch pitch copper in sea water containing hydrogen sulphide were investigated. Metal subjected to the action of sulphide was subsequently exposed to the harbour waters. The results indicated that in the putrid media corrosion rate of copper was low in the presence of high levels of sulphide and low levels of oxygen. These studies have also shown higher rate of corrosion on subsequent exposure to flowing sea water containing sulphide and dissolved oxygen.